Analisis Mekanisme Keamanan Antara TLS/SSL Dan Crypto Pada Komunikasi IoT Middleware Dengan Subscriber Berbasis Protokol HTTP - Deny Hari Prasetya Dewa; Eko Sakti Pramukantoro; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
There is a security hole in message delivery on a middleware where messages are still in plain text, causing data confidentiality to be insecure. Eavesdropping activities will be very easy to do if a security mechanism is not implemented immediately. Based on the problem, implemented end-to-end security mechanism using TLS / SSL and Crypto. The use of security mechanisms not only secures the network, but also affects the performance of the system. The process of encryption and decryption slows down middleware performance. This study focuses on knowing how the impact of TLS / SSL and Crypto security mechanisms, especially AES-256 on data security and middleware performance. Before the security mechanism is implemented, the data contained on the network is very readable. After both security mechanisms are implemented, the data cannot be known again because the contents have been encrypted. TLS / SSL provides stronger security by using certificate exchanges as an authentication system. Both methods installed are capable of securing the system but both affect the performance of middleware. Both security mechanisms have no significant effect on CPU and memory usage. AES-256 produces better values ​​on packet loss parameters, with a value of 1%. While TLS / SSL is superior in parameter delay and jitter, with value 0.089008423 sec and 0.003208877 sec.